Open-system orchestration as a relational source of sensing capabilities: evidence from a venture association - Giudici, Alessandro; Reinmoeller, Patrick; Ravasi, Davide (Academy of Management, 2017)
Research on innovation networks has highlighted the pivotal role that actors with more prominence and power, such as hub firms, may play in orchestrating the activities of other network members along a collective innovation effort. Our study examined the under-theorized, but no less important, type of orchestration that characterizes other organizations, such as business incubators and venture associations, who seek to support the dispersed entrepreneurial efforts of network members. We refer to this type as 'open-system' orchestration, as opposed to the commonly studied 'closed-system' type performed by hub firms. Our findings reveal how the processes of open-system orchestration differ markedly from those of closed-system orchestration, and detail how these processes influence the micro-foundations of network members' sensing capabilities. By doing so, we also offer empirical substantiation and theoretical elaboration to the idea that dynamic capabilities might not reside exclusively inside firms, but could be co-created relationally with other parties in the business ecosystem.
Keywords: network orchestration; dynamic capabilities; sensing; micro-foundations; network orchestration; dynamic capabilities; sensing; micro-foundations